Relationship between chronic hyperglycemia and contrast extravasation in revascularization of symptomatic intracranial atherosclerotic stenosis: A retrospective single-center study. (July 2021) - Zhu, Wanchun; Hua, Xuming; Liu, Zhenxing; Zhang, Xin; Li, Shiting; Jing, Chaohui
Highlights: Contrast extravasation is one of the most common complications after PTAS. Patient with chronic hyperglycemia is closely related to contrast extravasation. Chronic exposure to the abnormal blood glucose levels may impair the BBB. Abstract: Background and purpose: Contrast extravasation is one of the most common perioperative complications in symptomatic intracranial atherosclerotic stenosis (ICAS) patients after percutaneous transluminal angioplasty and/or stenting (PTAS). This study aimed to investigate the correlations between the relevant serum biochemical indicators of carbohydrate metabolism and the occurrence of contrast extravasation. Methods: Patients' demographic characteristics, vascular risk factors and laboratory examination data were collected. Blood routine test, blood biochemical examination and hormone level test within 1 week before surgery were measured in all enrolled subjects. Patients underwent non-contrast CT scans immediately after the endovascular procedure. Follow-up non-contrast CT scans were performed in the next 24 h and repeated as per clinical condition. Results: 104 patients who have undergone effective PTAS were involved in this study. 18 patients have identified as contrast extravasation and there was no obvious abnormality in another 86 cases. There were significant differences in the pre-operative HbA1c, fasting blood sugar and cortisol levels in the subjects regardless of gender between two groups ( p  < 0.001, p  < 0.001 and p  = 0.001, respectively). Furthermore, there were statistical differences in E2 and testosterone levels between two groups in both male population ( p  = 0.035 and p  = 0.028, respectively) and female population ( p  = 0.036 and p  = 0.003, respectively). Besides, the AUC value of HbA1c, fasting blood sugar and cortisol levels were all over 0.7 (0.858, 0.780 and 0.752, respectively). The highest AUC value of various combinations was obtained from the combination of HbA1c and cortisol level, which was 0.898. Conclusions: Patient with chronic hyperglycemia is closely related to contrast extravasation after PTAS. Specific mechanisms might be explored and regarded as promising candidates to prevent contrast extravasation.